Work Motivation of Persons With Disabilities in UMKM Arsyadina Surabaya (Descriptive Qualitative Study) - Gendut Sukarno; Mulik Khabibah (International Forum of Researchers and Lecturers, 2024)
This study uses a descriptive qualitative method to analyze the intrinsic and extrinsic work motivation of individuals with disabilities at UMKM Arsyadina in Surabaya. Data was collected through interviews, observations, and documentation involving several informants, including the owner, non-disabled employees, and employees with disabilities who have worked for approximately two years. The data obtained was then analyzed using data condensation techniques, data presentation, and conclusion drawing. The results of the analysis indicate that individuals with disabilities have high motivation to work, driven by both internal and external factors. Moreover, the inclusive and adaptive work environment at UMKM Arsyadina contributes significantly to enhancing their work enthusiasm. These findings provide valuable insights into the motivational factors that enable individuals with disabilities to perform well in the workplace.